Cloud Database Optimization: Strategies for Performance, Scalability, and Cost-Efficiency - Sunil Yadav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud database optimization encompasses technical strategies designed to enhance performance, ensure scalability, and control costs in modern cloud computing environments. The transition from traditional on-premises database management to cloud-based solutions presents organizations with significant advantages alongside complex optimization challenges. This article synthesizes findings from extensive implementations across various enterprise environments to quantify the impact of key optimization strategies. The article demonstrates that properly implemented query optimization techniques significantly reduce resource consumption and execution time, while advanced indexing strategies substantially decrease I/O operations and associated costs. Both horizontal and vertical database partitioning approaches provide dramatic performance improvements for large datasets, enabling consistent performance despite substantial growth in data volume. Elastic scaling capabilities allow organizations to perform optimally during workload fluctuations while avoiding unnecessary provisioning costs. Comprehensive monitoring combined with proactive alerting systems enables early detection of performance issues before they impact end-users, with automated maintenance procedures ensuring continued optimization. The collective implementation of these strategies yields substantial improvements in application responsiveness and user experience while simultaneously reducing operational expenditures, making cloud database optimization an essential discipline for organizations seeking to maximize the benefits of cloud computing.